2022
DOI: 10.3389/fneur.2022.889141
|View full text |Cite
|
Sign up to set email alerts
|

m6A regulator–mediated RNA methylation modification patterns and immune microenvironment infiltration characterization in patients with intracranial aneurysms

Abstract: BackgroundThe role of epigenetic modulation in immunity is receiving increased recognition—particularly in the context of RNA N6-methyladenosine (m6A) modifications. Nevertheless, it is still uncertain whether m6A methylation plays a role in the onset and progression of intracranial aneurysms (IAs). This study aimed to establish the function of m6A RNA methylation in IA, as well as its correlation with the immunological microenvironment.MethodsOur study included a total of 97 samples (64 IA, 33 normal) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Various studies demonstrate that high expression of LRPPRC is associated with poor prognosis in a variety of cancers, such as bladder urothelial carcinoma [39], lung cancer [40] and pancreatic cancer [41]. Maimaiti [42] et al de ned LRPPRC as a N6methyladenosine (m6A) modi cation for intracranial aneurysms. Ghavami S [43] et al reported that LRPPRC was associated with multiple neurodegenerative diseases via autophagy and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies demonstrate that high expression of LRPPRC is associated with poor prognosis in a variety of cancers, such as bladder urothelial carcinoma [39], lung cancer [40] and pancreatic cancer [41]. Maimaiti [42] et al de ned LRPPRC as a N6methyladenosine (m6A) modi cation for intracranial aneurysms. Ghavami S [43] et al reported that LRPPRC was associated with multiple neurodegenerative diseases via autophagy and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the mechanisms of m6A methylation [49] and immunogenic cell death [50] in IAs were also investigated. In the future, further investigation should be conducted on the mechanism of its role in IAs in DNA methylation and more epigenetic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Sva package was used to remove batch effect in raw data. A total of 64 IA samples and 33 normal samples were included 11 . Subsequently, a random split was performed using the caret package in a 7:3 ratio.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 64 IA samples and 33 normal samples were included. 11 Subsequently, a random split was performed using the caret package in a 7:3 ratio. The training set included 45 cases of aneurysm samples and 24 cases of normal samples.…”
Section: Datasets and Preprocessingmentioning
confidence: 99%